Response of Giving Liquid Organic Fertilizer (POC) Banana weevil to Growth and Production of Several Varieties of Chili (Capsicum frutenens L Var. Cengek) - Muhammad Alwi Ma'arif Ritonga; Fitra Syawal Harahap; Novilda Elizabeth Mustamu; Siti Hartati Yusida Saragih (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to determine the response of growth and production of several varieties of cayenne pepper (Capsicum frutencens L Var Cengek) to various concentrations of liquid organic fertilizer of banana weevil and whether or not the interaction between these two factors is significant. This research was carried out in the Mampang Village where the research was conducted starting from April 1, 2022 until its completion. The design used in this study was a 5 x 5 factorial randomized block design (RAK) with 3 replications. Factors studied include the concentration of liquid organic fertilizer banana weevil and varieties. The banana weevil POC concentration factor (K) consists of 6 levels, namely K0 = 0 (Control), K1 = 10% (100 ml POC / 900 ml water), K2 = 20% (200 ml POC / 800 ml water), K3 = 30% (300 ml POC/ 700 ml water), K4 = 40% (400 ml POC/ 600 ml water) and K5 = 50% (500 ml POC/ 500 ml water). The variety factor (V) consists of 3 levels, namely V1 = Genie, V2 = Genie, and V3 = Genie. The variables observed were plant height, stem diameter, number of fruit, fruit weight and production per hectare. The results of the F test on analysis of variance showed that the concentration of banana weevil POC had a very significant effect on stem diameters at 20 and 30 DAP, number of fruits, fruit weight and production per ha. Significant effect on plant height 20, 30 and 40 DAP, stem diameter 40 DAP. Varieties significantly affected plant height 30 and 40 DAP, stem diameter 20, 30 and 40 DAP, number of fruits, fruit weight and production per ha. However, it had no significant effect on plant height at 20 DAP. There was no interaction between the concentration of banana weevil POC and varieties on all observed variables.